Community Empowerment in the Digital Era : Developing Social Media Campaigns for OTOP Branding - Wulandari, Anna; Wahdiniwaty, Rahma; Catur Pamuji, Geraldi; Keawkanya, Chutima; Shiha, Osama; Aprilianti, Dhiani; Agustian, Aryanti; Farhan Aqsha, Muhammad (PT Inovasi Pratama Internasional, 2025)
Community empowerment through localized economic development is vital for sustainable growth, particularly in rural areas. This study focuses on developing and implementing social media campaigns to enhance the branding of One Tambon One Product (OTOP) in Bang Prong, Samut Prakan, Thailand. Employing a mixed-methods approach, the research combined community engagement, audience analysis, strategic campaign design, and comprehensive evaluation. The campaign leveraged storytelling, influencer partnerships, interactive content, and educational outreach to increase product visibility and consumer engagement. Results showed a substantial increase in social media reach, positive shifts in brand perception, and enhanced entrepreneurial confidence among community members. The campaign also fostered stronger social cohesion and promoted sustainable production practices. This study contributes to the understanding of digital marketing’s role in community-based economic initiatives and offers a replicable model for empowering grassroots enterprises in the digital era. The findings underscore the importance of integrating digital tools with traditional practices to drive inclusive and sustainable local development.